Preparing Primary School Teachers for Teaching Computational Thinking: A Systematic Review - Ausiku, Maria; Matthee, Machdel (Learning Technologies and Systems, 2021)
The purpose of this study is to systematically examine the existing literature on the teaching approaches and tools used to prepare primary school teachers to integrate computational thinking (CT) in their offering. In addition, the study considers perceptions of teachers towards teaching approaches for CT. Thirty (30) journal articles and conference proceedings that met the selection criteria were reviewed and thematically analysed. Teaching approaches and tools that have been used to train teachers on teaching CT in primary schools include unplugged computing, robotics, programming and game-based learning activities. Teachers’ perceptions toward the teaching approaches for integration of CT were positive and progressive after interventions. To support teachers, most studies introduced modules within teacher-education curriculum or a professional development course for in-service teachers. The results indicated that most of the integrations are done within mathematics and science classes. Also, coding remains a useful way to teach CT. To prepare teachers to teach CT concepts and skills, both pre-service and in-service teachers need to practice teaching those concepts in authentic contexts. The review highlights the need for research that addresses the developing country context and working context of teachers as teaching strategies would differ from the developed countries context which has dominated the current research done.